A Ricardian Analysis of the Impact of Climate Change on European Agriculture - Steven Van Passel; Emanuele Massetti; Robert O. Mendelsohn (Center for Economic Studies and ifo Institute (CESifo), 2014)
This research estimates the impact of climate on European agriculture using a continental scale Ricardian analysis. Climate, soil, geography and regional socio-economic variables are matched with farm level data from 37,612 farms across Western Europe. We demonstrate that a median quantile regression outperforms OLS given farm level data. The results suggest that European farms are slightly more sensitive to warming than American farms with losses from -8% to -44% by 2100 depending on the climate scenario. Farms in Southern Europe are predicted to be particularly sensitive, suffering losses of -9% to -13% per degree Celsius.
Keywords: Q54; Q51; Q15; 330; Ricardian analysis; climate change; European agriculture; climate change economics; quantile regression